ARMS – A NEW APPROACH TO CONTROL CONTENT SHARING AND RIGHTS DISTRIBUTION - Marques, J.; Serrão, C. (7th annual International Conference on Education and New Learning Technologies (EDULEARN15), 2015)
As in other areas, one of the main issues in the educational sector is related with content distribution and sharing. Ensuring that the terms and conditions stated by content owners on the license are respected by the other participants of the value chain, such as distributors (eg. teachers) or consumers (eg. students) is a concern. The assignment of licenses is a need in order to the distributor in the DRM system unambiguously communicate the licensing of the content giving an enhanced user experience. Not only is important to validate the issued license verifying if the terms and the conditions stated in the parental license are respected in the child license but also is important to verify if this license is generated to users that are in a controlled domain. In this paper we will describe our rights-sharing control mechanism based in MPEG-21 standard that augments the control over a domain (the institution educational domain) through the validation of the license to be generated. Through a specific DRM system oriented to the educational context (ARMS - Academic Rights Management System) content owners are allowed to control which users can obtain a license within the constraints imposed by him, giving them the power to control the content usage in the educational domain. To enable this feature some special control mechanism, MPEG-21 based, were implemented in order to control the license issuance. With these verification mechanisms is possible to make the license distributor act like a domain controller regulating the issuance of licenses in the educational context. Our proposal, when applied in the educational domain, greatly increases the expressive power of digital rights management framework without requiring an upgrade to end-user devices.